INDIAN BANKING SECTOR: ISSUES AND CHALLENGES - Sinagi, Bhagyashree K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian Banks are the platform of Indian economy. Banks are the lifeblood of the economy, acting as a catalyst to activate and sustain economic growth, particularly in developing nations such as India. It is critical that banks maintain their financial health. Otherwise, a country may face a financial crisis, resulting in a recession. The last decade has seen one of the most significant revolutions in financial institution culture and operations. The introduction of digital technology has opened the industry to new problems, rivals, and working methods. Banks in India are dealing with a variety of issues and challenges that have impacted their profitability and financial stability. The paper attempts to identify issues and challenges for the Indian banking system using secondary data.